Kepemimpinan Agile di Masa Ketidakpastian: Menerapkan Karakteristik AGILE untuk Keunggulan Kompetitif - Arfin, Antoni Ludfi; Wardana, Kun Wahyu; Nugroho, Joko (Efektor, 2024)
In an era characterized by intense competition and increasing complexity, organizations require agile leadership to survive and thrive. In response to the challenges posed by VUCA (Volatility, Uncertainty, Complexity, and Ambiguity), organizations must possess the capacity to adapt swiftly and effectively to emerging situations. This study aims to review the literature on agile leadership, focusing on five key characteristics: Adaptive, clear goal setting, Innovative, leading by action, and enthusiasm. The research employs a qualitative approach based on Cresswell & Cresswell's (2018) methodology, involving a review of 50 articles related to Agile Leadership. The findings reveal that agile leadership, which integrates the characteristics of adaptability, effective goal setting, innovation, leading by action, and enthusiasm. These characteristics are crucial for achieving long-term competitive advantage. Agile leadership enables organizations to navigate uncertainty and complexity more effectively, capitalize on opportunities, and ensure sustained success in a continuously evolving market.